مرزا داغ کے نعتیہ اسلوب کے اقبال پر اثرات: Impacts Of Mirza Dagh’s Nautiya Style On Iqbal’s Poetry - Rubab, Dr. Syeda Tayyeba; Abdullah, Hafiz Muhammad; Ullah, Dr Anwar (Al-Amīr Research Journal for Islamic Studies, 2023)
The linguist poet of the ambassador of Dehli literary society, Nwab Mirza Khan Dagh does not need any preamble. Iqbal accepted some artistic impacts of Mirza Dagh.He is a romantic poet but he was also effected by revolution of 1857.He narrated the cultural defeat in his poetry. We also can find the cultural defeat in Iqbal’s poetry as well. Iqbal paid tribute to Mirza Dagh at his death with deep grief and in an impressive way. As an artist, the use of developed language precision continuity and idiomatic phrases is Dagh’s distinctive style, the same style of Mirza Dagh is also available in his Nautiya poetry. Although it is not recognition of Dagh but his style is striking researchable. We can also come across the technical effects of his Nautiya style in Iqbal’s poetry. Iqbal has also saluted to his artistic climax. In this article the effort has been accomplished to explain Mirza Dagh’s impacts on Iqbal Keywords: Allama Iqbal, Mirza Dagh, Na‘at, poetry Praise of Prophet Muhammad ﷺ.